Breastfeeding Affects Concentration of Faecal Short Chain Fatty Acids During the First Year of Life: Results of the Systematic Review and Meta-Analysis - Łoniewski, Igor; Skonieczna-Żydecka, Karolina; Stachowska, Laura; Fraszczyk-Tousty, Magdalena; Tousty, Piotr; Łoniewska, Beata (Frontiers in Nutrition, 2022)
Short chain fatty acids (SCFAs) are important metabolites of the gut microbiota. It has been shown that the microbiota and its metabolic activity in children are highly influenced by the type of diet and age. Our aim was to analyse the concentration of faecal SCFAs over two years of life and to evaluate the influence of feeding method on the content of these compounds in faeces. We searched PubMed/MEDLINE/Embase/Ebsco/Cinahl/Web of Science from the database inception to 02/23/2021 without language restriction for observational studies that included an analysis of the concentration of faecal SCFAs in healthy children up to three years of age. The primary outcome measures-mean concentrations-were calculated. We performed a random-effects meta-analysis of outcomes for which ≥2 studies provided data. A subgroup analysis was related to the type of feeding (breast milk vs formula vs mixed feeding) and the time of analysis (time after birth). The initial search yielded 536 hits. We reviewed 79 full-text articles and finally included 41 studies (n=2457 SCFA analyses) in the meta-analysis. We found that concentrations of propionate and butyrate differed significantly in breastfed infants with respect to time after birth. In infants artificially fed up to 1 month of age, the concentration of propionic acid, butyric acid, and all other SCFAs is higher, and acetic acid is lower. At 1-3 months of age, a higher concentration of only propionic acid was observed. At the age of 3-6 months, artificial feeding leads to a higher concentration of butyric acid and the sum of SCFAs. We concluded that the type of feeding influences the content of SCFAs in faeces in the first months of life. However, there is a need for long-term evaluation of the impact of the observed differences on health later in life and for standardization of analytical methods and procedures for the study of SCFAs in young children. These data will be of great help to other researchers in analysing the relationships between faecal SCFAs and various physiologic and pathologic conditions in early life and possibly their impact on health in adulthood.